Public economic gains from tax-financed investments in childhood immunization in the United States. - Mark P Connolly; Nikolaos Kotsopoulos; Craig Roberts; Laurence Kotlikoff; David E Bloom; Tianyan Hu; Mawuli Nyaku (Public Library of Science (PLoS), 2023)
The emergence of COVID-19 has displayed the importance of immunization and the need for continued public investment in vaccination programs. Globally, national vaccination programs rely heavily on tax-financed expenditure, requiring upfront investments and ongoing financial commitments. To evaluate annual public investments, we conducted a fiscal analysis that quantifies the public economic consequences to government in the United States attributable to childhood vaccination. To estimate the change in net government revenue, we developed a decision-analytic model that quantifies lifetime tax revenues and transfers based on changes in morbidity and mortality arising from vaccination of the 2017 U.S. birth cohort. Reductions in deaths and comorbid conditions attributed to pediatric vaccines were used to derive gross lifetime earnings gains, tax revenue gains attributed to averted morbidity and mortality avoided, disability transfer cost savings, and averted special education costs associated with each vaccine. Our analysis indicates a fiscal dividend of $41.7 billion from vaccinating this cohort. The bulk of this gain for government reflects avoiding the loss of $30.6 billion in present-value tax revenues. All pediatric vaccines raise tax revenues by reducing vaccine-preventable morbidity and mortality in amounts ranging from $7.3 million (hepatitis A) to $20.3 billion (diphtheria) over the life course. Based on public investments in pediatric vaccines, a benefit-cost ratio of 17.8 was calculated for each dollar invested in childhood immunization. The public economic yield attributed to childhood vaccination in the U.S. is significant from a government perspective, providing fiscal justification for ongoing investment.